Estrogen-Related Receptor α Expression and Function Are Associated With Vascular Endothelial Growth Factor in Human Cervical Cancer. Issue 4 (1st April 2011) - Mori, Taisuke; Sawada, Morio; Kuroboshi, Haruo; Tatsumi, Hiroshi; Katsuyama, Masato; Iwasaku, Kazuhiro; Kitawaki, Jo
Abstract : Introduction: Estrogen-related receptor α (ERRα), one of orphan nuclear receptors with an unknown ligand, is expressed in various types of cancer. Increased ERRα levels are associated with a higher risk of recurrence and poor clinical outcome in breast cancer, suggesting that ERRα could be a negative prognostic factor. Recently, it has been suggested that vascular endothelial growth factor (VEGF) could be one of the transcriptional targets of ERRα in breast cancer. Here, we examined the expression of ERRα and the association of ERRα with VEGF in uterine cervical cancer cells and tissues. Methods: We evaluated the expression of ERRα and VEGF by immunohistologic analysis using specimens from 40 patients with invasive cervical cancer. We also evaluated the VEGF promoter activity of ERRα in cervical cancer cell lines by transfection and luciferase assay. We overexpressed or knocked down ERRα and examined VEGF expression by real-time polymerase chain reaction. Finally, cell proliferation assay was performed to examine whether ERRα affects tumor growth in cervical cancer. Results: Immunohistologic analysis demonstrated that ERRα expression in cervical cancer tissues was higher than that in noncancerous tissues and that there was a positive association between ERRα and VEGF expression in cancer tissues ( P < 0.05). We showed that ERRα stimulated the VEGF promoter activity in cervical cancer cell lines. We further showed the overexpression and knockdown of ERRα-regulated VEGF expression level by real-time polymerase chain reaction. Moreover, we showed that ERRα and VEGF knockdown by small interfering RNA or an inverse agonist of ERRα, XCT 790, could suppress cell growth compared with control cells in cervical cancer. Conclusions: We have provided compelling evidence that ERRα affects VEGF expression and tumor growth in cervical cancer. These results justify further investigation into the use of ERRα as a therapeutic target for patients with uterine cervical cancer.